The effect of omission of adjuvant radiotherapy after neoadjuvant chemotherapy and breast conserving surgery with a pathologic complete response. (2nd October 2020) - Mandish, Steven F.; Gaskins, Jeremy T.; Yusuf, Mehran B.; Amer, Yomna M.; Eldredge-Hindy, Harriet
Abstract: Objective(s): Neoadjuvant chemotherapy (NAC) is a standard of care for locally advanced breast cancers. Adjuvant radiotherapy (RT) after NAC is an area of active research. We hypothesize overall survival (OS) is not altered by omitting RT in women with a pathologic complete response (pCR) to NAC after breast conserving survery (BCS). Methods: Patients from the National Cancer Database who underwent NAC, BCS, and had a pCR were included. Inflammatory disease, <6 months follow up, and unknown variables were excluded. Descriptive statistics characterized the retained cohort. Logistic regression analyzed the influence of variables on the rate of RT omission. Cox proportional hazard modeling analyzed the influence of prognostic variables on OS. Results: Of 5383 women included, 364 (7%) omitted RT. 5-year OS was 94.1% with RT, 93% without. RT omission was most likely in women >70yo (adjusted OR2.4, 95%CI 1.58–3.65, p < .0001;reference 40–49 yo), Hispanic (AOR 1.73, 95%CI 1.19–2.52, p = .0044; reference non-Hispanic), ≥20 miles from treatment facility (20–49 miles; AOR 1.45, 95%CI 1.09–1.93, p = .0109: >50 miles; AOR 2.02, 95%CI 1.42–2.87, p < .0001;reference 0–19 miles), grade 1 (AOR 4.29, 95%CI 2.16–8.51, p < .0001; reference grade 3), and clinical T4 disease (AOR 3.17, 95%CI 1.74–5.79, p = .0002; reference T0/1). Women ≥60yo (60–69: AHR 2.33, 95%CI 1.41–3.83, p = .0009:70+:AHR 2.4, 95%CI 1.24–4.62, p = .0092; reference 40–49) and with N1 and N3 disease (N1: AHR 1.67, 95% CI 2.28–3.24, p = .0034; N3: AHR3.37, 95%CI2.01–5.65, p < .0001) showed increased death. Triple-positive (AHR 0.18, 95%CI 0.07–0.43, p = .0002) and HER2+ patients (AHR 0.44, 95%CI 0.30–0.64, p < .0001) had improved OS compared to triple-negative disease. No survival difference was seen with omission of RT (log-rank test: p = .1783; Cox model AHR 1.33, 95%CI 0.76–2.31, p = .3181). Conclusion: Women ≥70, of Hispanic origin, living ≥20 miles from treatment facility, and grade 1 disease were more likely to omit RT. HER2+ patients had favorable OS, while older age and N3 disease were negative prognostic factors. Omitting RT after a pCR to NAC and BCS was not found to affect OS.